2021
DOI: 10.1177/1558944721994265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hand Malformations in Patients With Moebius Syndrome and Their Management

Abstract: Background: Moebius syndrome is a disorder characterized by facial and abducens nerve paralysis. Patients can present a wide range of upper extremity malformations. Literature focused on orthopedic manifestations of Moebius syndrome shows variability in the prevalence and clinical presentation of upper extremity anomalies. The aim of this work is to evaluate the prevalence of upper extremity malformations in patients with Moebius syndrome, clarify its various clinical presentations, and present treatment strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A vascular disruption process involving the subclavian and vertebral arteries, or their branches, is the most widely accepted nongenetic etiology hypothesis for Moebius syndrome, and aligns with the suspected etiology of Poland anomaly and Klippel-Feil anomaly (Bavinck et al, 1986). One study demonstrated that 16% of patients with Moebius syndrome also had an upper extremity anomaly, with Poland anomaly the most commonly observed (Telich-Tarriba et al, 2021).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A vascular disruption process involving the subclavian and vertebral arteries, or their branches, is the most widely accepted nongenetic etiology hypothesis for Moebius syndrome, and aligns with the suspected etiology of Poland anomaly and Klippel-Feil anomaly (Bavinck et al, 1986). One study demonstrated that 16% of patients with Moebius syndrome also had an upper extremity anomaly, with Poland anomaly the most commonly observed (Telich-Tarriba et al, 2021).…”
Section: Resultsmentioning
confidence: 90%
“…A vascular disruption process involving the subclavian and vertebral arteries, or their branches, is the most widely accepted nongenetic etiology hypothesis for Moebius syndrome, and aligns with the suspected etiology of Poland anomaly and Klippel‐Feil anomaly (Bavinck et al, 1986). One study demonstrated that 16% of patients with Moebius syndrome also had an upper extremity anomaly, with Poland anomaly the most commonly observed (Telich‐Tarriba et al, 2021). The vascular disruption hypothesis is further supported by animal studies demonstrating cranial nerve damage after prenatal ischemic insults, as well as evidence of brainstem calcifications on head CT scans in several children with Moebius syndrome, suggesting an ischemic event in utero (Dooley et al, 2004; Lipson et al, 1989; J. R. Miller & Myers, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings agree with what has been reported in the literature. A cross-sectional study evaluating the prevalence of upper extremity malformations in 25 patients with MS showed that the most frequent were syndactyly (32%), brachysyndactyly (20%), and amniotic band syndrome (12%) [ 39 ]. Regarding ocular manifestations, another study found a higher prevalence of esotropia, abduction limitation, and compound hypermetropic astigmatism in patients with this syndrome [ 40 ].…”
Section: Discussionmentioning
confidence: 99%